Medical students, spirituality and religiosity-results from the multicenter study SBRAME - Lucchetti, Giancarlo (BioMed Central, 2013)
BACKGROUND: To evaluate the relationship between spirituality/religiosity (S/R) and the attitudes, beliefs and experiences of medical students in Brazil with respect to S/R in their undergraduate training and clinical practice. METHODS: SBRAME (Spirituality and Brazilian Medical Education) is a multicenter study involving 12 Brazilian medical schools with 5950 medical students (MS). Participants completed a questionnaire that collected information on socio-demographic data and S/R in their undergraduate training and practice. RESULTS: Of all MS, 3630 participated in the survey (61.0%). The sample was 53.8% women and the mean age was 22.5 years. The majority of MS believed that spirituality has an impact on patients’ health (71.2%) and that this impact was positive (68.2%). The majority also wanted to address S/R in their clinical practice (58.0%) and considered it relevant (75.3%), although nearly one-half (48.7%) felt unprepared to do so. Concerning their training, most MS reported that they had never participated in a “spirituality and health” activity (81.0%) and that their medical instructors had never or rarely addressed this issue (78.3%). The majority also believed that they should be prepared to address spiritual issues related to the health of their patients (61.6%) and that this content should be included in the medical curriculum (62.6%). CONCLUSION: There is a large gap between MS attitudes and expectations and the S/R training that they are receiving during their undergraduate training. The majority of MS surveyed believe that patients should have their beliefs addressed and that these beliefs could have important effects on their health and the doctor-patient relationship. These results should stimulate discussion about the place that S/R training should have in the medical curriculum.